1987
DOI: 10.1136/pgmj.63.746.1033
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic neuropathy in an alcoholic population

Abstract: Summary: Autonomic nervous system integrity has been assessed in 30 alcoholic subjects and 30 agesex matched controls using five simple tests of cardiovascular responses. There was evidence of parasympathetic neuropathy alone in five of the alcoholic subjects (16%) and of combined parasympathetic and sympathetic neuropathy in an additional six (20%). None ofthe controls showed any abnormality. Within the alcoholic group, those with autonomic neuropathy were older, were more likely to be female and to have esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 6 publications
(1 reference statement)
1
32
2
1
Order By: Relevance
“…Heart rate response to Valsalva manuoevre and postural drop in blood pressure were highly specific but of low sensitivity.8 patients had abnormal heart rate response to deep breathing ,8 patients had abnormal blood pressure response to sustained handgrip and 7 patients had abnormal Valsalva ratio. 1 The association of cardiovascular autonomic dysfunction (CAD) and Child -Pugh class of liver cirrhosis was not found to be statistically significant in the present study. In this study, according to Ewing,s criteria of severity of CAD,31(51.7%) had early,21(35%) cases had definite and 3 (5%) cases had severe CAD.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…Heart rate response to Valsalva manuoevre and postural drop in blood pressure were highly specific but of low sensitivity.8 patients had abnormal heart rate response to deep breathing ,8 patients had abnormal blood pressure response to sustained handgrip and 7 patients had abnormal Valsalva ratio. 1 The association of cardiovascular autonomic dysfunction (CAD) and Child -Pugh class of liver cirrhosis was not found to be statistically significant in the present study. In this study, according to Ewing,s criteria of severity of CAD,31(51.7%) had early,21(35%) cases had definite and 3 (5%) cases had severe CAD.…”
Section: Resultscontrasting
confidence: 68%
“…observed that alcoholics with liver damage have higher frequency of neuropathy than those without it. 1 There are reports of association of chronic liver disease with autonomic neuropathy. 2 Autonomic dysfunction can be primary or secondary, acute or chronic, and transient or progressive.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular autonomic neuropathy has been repeatedly reported in patients with primary diabetes mellitus [26,27] as well as in patients with history of chronic alcohol abuse [28,29]. In a previous study [8] we detected a high proportion of ARCP patients with cardiovascular autonomic neuropathy, and found that autonomic neuropathy was more frequent and more severe when ARCP was associated with diabetes mellitus, suggesting that alcohol and diabetes mellitus have additive effects in causing autonomic neuropathy.…”
Section: Discussionmentioning
confidence: 83%
“…It is well known that alcohol and diabetes mellitus can cause peripheral and autonomic neuropathy [26][27][28][29]. Previous studies on GI transit in chronic pancreatitis [1,3] did not include any patients with diabetes or alcohol abuse, while other studies [4,5] had only a few patients with diabetes mellitus and ARCP.…”
Section: Discussionmentioning
confidence: 97%
“…While alcoholics are generally prone to develop damages of the autonomous nervous system [2,7,22,27,29,33], in this study damages were rare even in unequivocally correctly classified younger alcoholics with a long duration of drinking and without accompanying diseases, compared to an age-matched group of diabetics with a comparable duration of disease. These two metabolic toxic neuropathies thus show different profiles of nerve damage.…”
Section: Discussionmentioning
confidence: 93%